Cameroon : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this study, the following statistical data are presented in detail: income, savings, and net financial balances, production of principal food crops, production of main cash commodities, capacity utilization in the industrial sector, petroleum product price structure, prices of major utilities, oil sector indicators, monetary survey, balance of payments, principal imports and exports, functional classification of government's expenditure, forestry sector indicators, structure of interest rates, trade and exchange arrangements, government employment and average salaries by sector, economic classification of government expenditure, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet